An investigation of binary stars in the Pleiades with high contrast and spatial resolution - Richichi A. (2014)
Context. It is widely recognized that binarity is a very common feature during star formation; however, different regions and clusters display significantly different binary fractions. This appears to be related to the initial density of the star forming region. The Pleiades cluster has been shown to have a binary fraction similar to that of field stars in the solar neighborhood. Aims. We have taken advantage of a passage of the Moon over the Pleiades cluster, to investigate at high angular resolution two small but similar and consistent samples of cluster members and field stars. Methods. We have employed the technique of lunar occultations (LO). Although LO in the Pleiades have been reported several times in the past, we have for the first time employed the superior performance of the VLT, achieving about 1 milliarcsecond (mas) resolution and detecting sources as faint as K ≈ 12 mag. Results. We have recorded 17 LO light curves of stars recognized as cluster members, and 17 of field stars. The average magnitude was K ≈ 8.5 mag and the average limiting resolution ≈0′′.002, for both samples. We detect 5 binaries among the cluster members, and 2 among the sample of field stars. Three systems are new detections, while two were previously only suspected to be binaries. The projected separations are in the range 0.′′017 to 0.′′642 and the brightness ratios in the range 1 to 90. One more star is suspected to have a companion. Conclusions. Although the fraction of binary detections appears higher among the members than among the non-members, the two samples are too small to draw firm conclusions. Our observations show that, in spite of extensive investigations carried out previously in the Pleiades cluster, the binarity census is not yet complete. We have detected significant orbital motion in four binary systems, which stand up as candidates for dynamical mass estimations. © 2012 ESO.